Cystic renal masses: An imaging update. Issue 99 (February 2018) - Ward, Ryan D.; Remer, Erick M.
Highlights: Recognition that cystic renal malignancies are generally indolent has led to recommendations for less aggressive management. The Bosniak classification is useful to stratify risk of malignancy in cystic renal masses. Many different pathologies, both benign and malignant, present as cystic renal masses on imaging. Some have distinctive demographic and imaging appearances. Abstract: Management of incidental renal masses is in evolution. Recognition that cystic renal tumors generally act in an indolent fashion has led to less aggressive intervention. The ability of radiologists to stratify risk of malignancy, and in some cases, specify a precise diagnosis, is paramount to patient management. We review pathologies that present as cystic renal masses and how to best stratify malignancy risk.